APPLICATION OF GRAPHITES IN ELECTRICALLY CONDUCTIVE POLYMER COMPOSITES - БУТЕНКО, О. О.; ЧЕРНИШ, О. В.; КУБАЙ, Ю. О.; ХОМЕНКО, В. Г.; БАРСУКОВ, В. З.; КУРИПТЯ, Я. А. (Technologies and Engineering, 2023)
Purpose: Study of the influence of the physical properties of natural graphites on the electrical conductivity of polymer coatings. Methodology: The geometrical parameters of particles of different-dispersed graphites were studied by optical and electron microscopy. The change in the spatial electrical conductivity of graphite powders under the action of an external load was determined using a specially made cell. Taking into account the anisotropic physical properties of graphite crystals, dispersed carbon black was added to the polymer binder during the manufacture of composites. Dispersion was carried out using ultrasound in an alcohol medium. A 10% solution of polyvinyl butyral in ethanol was used as a binder for dispersed components. The thickness of the composite on a solid surface was set using an applicator. The surface electrical conductivity was recorded by the four-electrode method. Findings: The dependence of the surface electrical conductivity of polymer composites on the size, shape and polydispersity of graphite particles was studied. When obtaining polymer coatings based on graphite by the paint and varnish method, a significant orientation of two-dimensional mineral particles occurs, which has a significant effect on the spatial electrical conductivity of the composite. The factor limiting the electrical conductivity of polymer coatings based on coarse graphite is micropores and small cracks due to low compaction of such particles and a large volume of ethanol in a 10% polymer binder solution. Ultrasound under certain conditions leads to delamination of graphite particles, which contributes to an increase in the electrical conductivity of composite coatings. Scientific novelty: It has been established that with an increase in the size and a decrease in the polydispersity of particles of flake graphite, the surface electrical conductivity of the polymer coating increases. Adding a composite of dispersed carbon or inorganic additives reduces this electrical conductivity. Practical value: The increase in the surface electrical conductivity of polymer composites in shielding devices contributes to the effectiveness of protecting humans and electronics from the negative effects of electromagnetic radiation.